2006
DOI: 10.1155/jammc/2006/67571
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Automated Sequential‐Injection Analyser for Dual Electrogenerated Chemiluminescence/Amperometric Detection

Abstract: This work describes the development of a dedicated, fully automated sequential-injection analysis (SIA) apparatus suitable for simultaneous electrogenerated chemiluminescence (ECL) and amperometric detection. The instrument is composed of a peristaltic pump, a multiposition selection valve, a home-made potentiostat, a thin-layer electrochemical/optical flow-through cell, and a light detector. Control of the experimental sequence and simultaneous data acquisition of the light and the current intensities were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Wilson et al , recently reported a flow injection electrochemiluminometer either with (Figure ) or without a magnet in the flow cell for enzyme immunoassays of explosives 2,4,6-trinitrotoluene (TNT) and pentaerthyritol tetranitrate (PETN). Also, a fully automated sequential injection analyzer for simultaneous ECL and amperometric detection has been described . The instrument is composed of a peristaltic pump, a multiposition selection valve, a homemade potentiostat, a thin-layer electrochemical/optical flow-through cell, and a light detector (Figure ).…”
Section: Ecl Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Wilson et al , recently reported a flow injection electrochemiluminometer either with (Figure ) or without a magnet in the flow cell for enzyme immunoassays of explosives 2,4,6-trinitrotoluene (TNT) and pentaerthyritol tetranitrate (PETN). Also, a fully automated sequential injection analyzer for simultaneous ECL and amperometric detection has been described . The instrument is composed of a peristaltic pump, a multiposition selection valve, a homemade potentiostat, a thin-layer electrochemical/optical flow-through cell, and a light detector (Figure ).…”
Section: Ecl Instrumentationmentioning
confidence: 99%
“…(b) Schematic diagram of the electrochemical/optical flow-through cell. Reprinted with permission from ref. 2006 Hindawi.…”
Section: Ecl Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, published papers describe such LabVIEW ® -based software for the automation of specific analytical systems such as flow injection analysis (FIA) [ 8 ], sequential injection analysis (SIA) [ 9 ] or capillary electrophoresis (CE) [ 1 ]. Applications include automatic liquid handling, treatment, separation and, in some cases, detection of the interest analyte.…”
Section: Introductionmentioning
confidence: 99%